The Messianic Violence of Jesus - García Martínez, Francisco (Razón y fe, 2025)
After showing how violence is an attempt to realise one’s own identity by annulling that of the other, the reflection focuses on Jesus’ praxis in the face of it. Although his messianic action is belligerent and harsh, in a way that could be understood as violent, its paradoxical purpose is to reveal and dismantle the systems that hide the real violence that nullifies the identity of many through systems of social stigmatisation. This action will generate a reactive violence that Jesus accepts to bear by showing a paradoxical way of maintaining his own salvific identity. The ‘violence’ of his ministry appears then as a limiting action of social regeneration and salvation.
Keywords: Christology; messianism; violence; victim; cross; peace